HUBUNGAN ANTARA ESG DAN KINERJA KEUANGAN - Arsal, Muryani; Ardhana, Chindy Putri; Amaliah , Nur Fitri; Zainal , Andi Maghfirah (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study aims to analyze the impact of (ESG) performance disclosure on corporate financial performance. Employing a systematic literature review approach, the research evaluates recent literature that utilizes secondary data, such as annual reports and ESG scores from independent institutions. The analysis reveals that ESG implementation positively influences operational efficiency, attracts investor interest, and enhances corporate market value. The governance aspect consistently demonstrates a significant contribution to financial performance, while the Environmental aspect exhibits more variable positive effects depending on the industrial sector. On the other hand, the Social aspect produces mixed outcomes. This study highlights the challenges of ESG implementation in Indonesia, including the lack of uniform reporting standards and regulatory complexities, but underscores its potential benefits in enhancing business sustainability. The practical implications of this research emphasize the need for integrated ESG strategies to maximize long-term corporate value and meet stakeholder expectations.